Counteraction to the Investigation of Crimes: The Concept, the Types and the Ways of Overcoming - ABDULLINA, Sabina Kh.; KAN, Aleksandr G. (Journal of Advanced Research in Law and Economics; Vol 8 No 5 (2017): JARLE Volume VIII Issue 5(27) Fall 2017, 2018)
The concept of counteraction to the investigation of crimes, its classification by subjects, types, forms and methods of rendering, as well as other classification characteristics, are studied in this article. A systematic analysis of the criminal and criminal procedural legislation of the Republic of Kazakhstan related to the overcoming of the counteraction to the investigation of crimes is performed by the authors. Through the conducted scientific analysis, the problems related to the concept of counteraction to the investigation of crimes, as well as its use in special legal literature, are revealed. The main components, characterizing the counteraction to the investigation of crimes, are identified in this study; the authors' definition of such counteraction is formulated, and the measures to overcome it are developed. Based on the results of the study, the authors come to the conclusion that the improvement of the current legislation in the sphere of counteraction to the investigation of crimes, the further scientific development in this field, the development of methods and instructions for law enforcement officers to overcome the counteraction to the detection and investigation of crimes, as well as the improvement of their professional skills, are required.